2017
DOI: 10.15836/ccar2017.6
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Work of Croatian Invasive Cardiologic Laboratories between 2010 and 2014

Abstract: SAŽETAK: Uz napredak intervencijske kardiologije u Republici Hrvatskoj unatrag dva i pol desetljeća svrha je ovog rada bila analizirati broj i složenost perkutanih koronarnih intervencija (PCI) u pojedinim centrima. Od 2010. do 2014. u ukupno 13 centara prosječno su učinjena 9494 PCI-ja godišnje. Sedam centara svrstavamo u velike, Kliniku Magdalena s najvećim brojem PCI-ja svake godine i prosječnim godišnjim rastom od 6,2 % (s 1545 na 1941 PCI-ja), slijedi Klinički bolnički centar (KBC) Zagreb u kojem se bilje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Availability of new-generation stents and drug-eluting balloons required for optimal efficacy and safety of interventional cardiology has also been upgraded. 21,22 At the same time, the quality of prescribing and outpatient use of cardiovascular drugs has been improved 23 , confirming the results from randomized studies and guidelines to have been implemented in daily clinical routine.…”
Section: Raspravamentioning
confidence: 54%
See 1 more Smart Citation
“…Availability of new-generation stents and drug-eluting balloons required for optimal efficacy and safety of interventional cardiology has also been upgraded. 21,22 At the same time, the quality of prescribing and outpatient use of cardiovascular drugs has been improved 23 , confirming the results from randomized studies and guidelines to have been implemented in daily clinical routine.…”
Section: Raspravamentioning
confidence: 54%
“…Veća je dostupnost novih generacija stentova i balona s otpuštanjem lijeka nužnih za optimalne rezultate intervencijske kardiologije glede učinkovitosti i sigurnosti. 21,22 Istodobno je utvrđena povećana kvaliteta propisivanja i izvanbolničke potrošnje kardiovaskularnih lijekova 23 , što potvrđuje da se rezultati iz randomiziranih istraživanja i smjernica primjenjuju u svakodnevnoj kliničkoj praksi.…”
Section: Raspravaunclassified
“…A systematic review and meta-analysis carried out by Kamarullah et al showed an even higher global drop in STEMI admissions during the pandemic, reaching up to 80% in some circumstances [ 11 ]. Data from Croatia demonstrated a relatively modest decline in STEMI admissions compared to other countries, likely due to the well-established national primary PCI network [ 12 ]. A fall in the number of admitted NSTEMI patients was also recorded worldwide, from 33% to 66% [ 7 , 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%